Third-generation taxanes SB-T-121605 and SB-T-121606 are effective in pancreatic ductal adenocarcinoma - Sychra, Tomas; Spalenkova, Alzbeta; Balatka, Stepan; Vaclavikova, Radka; Seborova, Karolina; Ehrlichova, Marie; Truksa, Jaroslav; Sandoval-Acuña, Cristian; Nemcova, Vlasta; Szabo, Arpad; Koci, Kamila; Tesarova, Tereza; et al. (iScience, 2024)
Pancreatic cancer is a severe malignancy with increasing incidence and high mortality due to late diagnosis and low sensitivity to treatments. Search for the most appropriate drugs and therapeutic regimens is the most promising way to improve the treatment outcomes of the patients. This study aimed to compare (1) in vitro efficacy and (2) in vivo antitumor effects of conventional paclitaxel and the newly synthesized second (SB-T-1216) and third (SB-T-121605 and SB-T-121606) generation taxanes in KRAS wild type BxPC-3 and more aggressive KRAS G12V mutated Paca-44 pancreatic cancer cell line models. In vitro, paclitaxel efficacy was 27.6 ± 1.7 nM, while SB-Ts showed 1.7-7.4 times higher efficacy. Incorporation of SB-T-121605 and SB-T-121606 into in vivo therapeutic regimens containing paclitaxel was effective in suppressing tumor growth in Paca-44 tumor-bearing mice at small doses (≤3 mg/kg). SB-T-121605 and SB-T-121606 in combination with paclitaxel are promising candidates for the next phase of preclinical testing.
Keywords: Pharmacology; Cell biology; Cancer